Muslim reformers in Iran and Turkey : the paradox of moderation - Tezcür, Güneş Murat, 1979- (Modern Middle East series (Austin, Tex.) ;, 2010)
Moderation theory describes the process through which radical political actors develop commitments to electoral competition, political pluralism, human rights, and rule of law and come to prefer negotiation, reconciliation, and electoral politics over provocation, confrontation, and contentious action. Revisiting this theory through an examination of two of the most prominent moderate Islamic political forces in recent history Muslim Reformers in Iran and Turkey analyzes the gains made and methods implemented by the Reform Front in the Islamic Republic of Iran and the Justice and Development Party in Turkey.